Revisiting the Impacts of the Economic Crises on Achieving the MDG 4 - Blanco-Arana, María del Carmen (Universidad de Huelva, 2019)
Well into the XXI century, child mortality is still high in developing countries. The Millennium Declaration approved at the United Nations Millennium Summit held in September 2000 set down, as its fourth objective, the reduction of child mortality by two thirds; from the 93 children per 1,000 that died before the age of 5 in 1990, to 42 per 1,000 in 2015. To this end, considerable advances have been made although the proposed goal is still a long way off in some countries and regions. In this context, the financial crisis of 2007–08 has, in addition, posed a serious threat to attaining this objective. In general terms, the recessionary phases of such cycles negatively impact the progress and welfare of countries with economic, political and social consequences for the population in general, and particularly for children. Therefore, the principal objective of this paper is to revisit the main impact of the last global economic decline on the more vulnerable children of countries of the South, with a special focus on the goal proposed by the fourth Millennium Development Goal (MDG), given that it presently constitutes a great challenge for the whole population within the framework of the Sustainable Development Goals (SDGs).
Política de acceso abierto de la revista: https://dulcinea.opensciencespain.org/ficha1392
Keywords: Crisis económicas; Economic crisis; Child mortality; MDG; SDG; Great Recession